Adult child socio-economic status disadvantage and cognitive decline among older parents in Mexico. (June 2021) - Torres, Jacqueline M.; Yahirun, Jenjira J.; Sheehan, Connor; Ma, Mingming; Sáenz, Joseph
Abstract: There is growing interest in the contribution of offspring educational attainment to parents' health outcomes. However, less is known about the impacts of offspring socio-economic status (SES) on parents' cognitive decline or about the role of offspring SES disadvantage . We used data from the Mexican Health and Aging Study (n = 10, 426) to evaluate the impact of adult child SES disadvantage on parents' verbal memory trajectories over fourteen years (2001–2015). We estimated linear mixed models and used measures of adult child SES (educational, financial, and employment) disadvantage. Our most robust finding was that having an adult child with less than secondary education was associated with faster decline in verbal memory z-scores for older women (β: −0.009 [95% CI: −0.01, −0.001]) and men (β: −0.01 [95% CI: −0.02, −0.01]). Although poor adult child financial well-being was associated with a faster decline in parents' verbal memory z-scores, this finding was less consistent across model specifications. Additional analyses also suggested some evidence of heterogeneity by parents' own educational attainment and gender. These findings highlight the potential importance of children's socio-economic status for the cognitive aging of their older parents. Highlights: Offspring socioeconomic advantage has been linked to parents' cognitive aging. No studies have evaluated the influence of offspring socioeconomic disadvantage. We assessed offspring disadvantage in education, financial status, and employment. Offspring educational disadvantage was associated with parents' memory decline.